A histochemical approach to activity-based copper sensing reveals cuproplasia-dependent vulnerabilities in cancer - Marco S. Messina; Laura Torrente; Aidan T. Pezacki; Hanna I. Humpel; Erin L. Li; Sophia G. Miller; Odette Verdejo-Torres; Teresita Padilla-Benavides; Donita C. Brady; David W. Killilea; Alison N. Killilea; Martina Ralle; et al. (Proceedings of the National Academy of Sciences, 2025)
Copper is an essential nutrient for sustaining vital cellular processes spanning respiration, metabolism, and proliferation. However, loss of copper homeostasis, particularly misregulation of loosely bound copper ions which are defined as the labile copper pool, occurs in major diseases such as cancer, where tumor growth and metastasis have a heightened requirement for this metal. To help decipher the role of copper in the etiology of cancer, we report a histochemical activity-based sensing approach that enables systematic, high-throughput profiling of labile copper status across many cell lines in parallel. Coppermycin-1 reacts selectively with Cu(I) to release puromycin, which is then incorporated into nascent peptides during protein translation, thus leaving a permanent and dose-dependent marker for labile copper that can be visualized with standard immunofluorescence assays. We showcase the utility of this platform for screening labile Cu(I) pools across the National Cancer Institute’s 60 (NCI-60) human tumor cell line panel, identifying cell types with elevated basal levels of labile copper. Moreover, we use Coppermycin-1 to show that lung cancer cells with heightened activation of nuclear factor-erythroid 2-related factor 2 (NRF2) possess lower resting labile Cu(I) levels and, as a result, have reduced viability when treated with a copper chelator. This work establishes that methods for labile copper detection can be used to assess cuproplasia, an emerging form of copper-dependent cell growth and proliferation, providing a starting point for broader investigations into the roles of transition metal signaling in biology and medicine.